Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Hidup Pada Diabetes Tipe 2 - Shanty Chloranita (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Diabetes is a chronic disease that requires the management of diabetes for a long time thus affecting the quality of life. This study aims to analyze the quality of life in type 2 diabetes. Cross sectional study design with a sample of 51 patients with type 2 diabetes with purposive sampling technique. The measuring instruments used are Diabetes Quality of Life Brief (DQoL Brief), Diabetes Self Management Questionnaire (DSMQ), Center for Epidemiologic Studies Depression Scale (CES-D). Bivariate analysis using pearson showed factors affecting quality of life in type 2 diabetes showing age (p value = 0.000), gender (p value = 0.137), complication (p value = 0.230), financing support (p value = 0.769) , treatment (p value = 0.310), diabetes self-management (p value = 0.290). Multivariate analysis using multiple linear regression with the most dominant factor modeling give influence to quality of life is age (beta value = 0.284). It is expected that nursing interventions are more optimal to improve the quality of life of diabetic patients.